The impact of snares on the continuity of adolescent-onset antisocial behaviour: A test of Moffitt's developmental taxonomy. Issue 3 (September 2015) - McGee, Tara Renae; Hayatbakhsh, Mohammad R; Bor, William; Aird, Rosemary L; Dean, Angela J; Najman, Jake M
Moffitt's dual typology of 'life-course persistent' and 'adolescence limited' offending has received extensive empirical attention, but the extent to which the antisocial behaviour of adolescence limited offenders is constrained to adolescence is relatively under-examined. Using data from the Australian Mater University Study of Pregnancy and its Outcomes, we explore Moffitt's concept of snares, or those factors that may lead to an adolescent persisting in antisocial behaviour such as drug addiction, educational failure, and contact with the justice system. The Mater University Study of Pregnancy and its Outcomes is a longitudinal study of mother–child dyads from the pre-natal stage to 21 years of age. Findings show that one-third of individuals identified as having an adolescent onset of antisocial behaviour persisted with this antisocial behaviour as young adults. This continuity can, in part, be explained by snares and the research suggests that reducing exposure to snares may lead to less antisocial behaviour in adulthood.